2018
DOI: 10.1111/pce.13471
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and molecular mechanisms of heavy metal accumulation in nonmycorrhizal versus mycorrhizal plants

Abstract: Uptake, translocation, detoxification, and sequestration of heavy metals (HMs) are key processes in plants to deal with excess amounts of HM. Under natural conditions, plant roots often establish ecto‐ and/or arbuscular‐mycorrhizae with their fungal partners, thereby altering HM accumulation in host plants. This review considers the progress in understanding the physiological and molecular mechanisms involved in HM accumulation in nonmycorrhizal versus mycorrhizal plants. In nonmycorrhizal plants, HM ions in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(49 citation statements)
references
References 174 publications
(230 reference statements)
2
46
0
1
Order By: Relevance
“…The much higher proportion of HSPs in non-mycorrhizal V. myrtillus roots may reflect the higher Cd content. A similar up-regulation of the GSH biosynthetic pathway has been reported in AM plants exposed to Cd (Huang et al, 2017;Shi et al, 2019), and it was suggested by these authors that AM fungi might attenuate Cd stress by enhancing the production of thiolic compounds in AM roots.…”
Section: Responses Of V Myrtillus Roots To Cd Exposuresupporting
confidence: 75%
See 1 more Smart Citation
“…The much higher proportion of HSPs in non-mycorrhizal V. myrtillus roots may reflect the higher Cd content. A similar up-regulation of the GSH biosynthetic pathway has been reported in AM plants exposed to Cd (Huang et al, 2017;Shi et al, 2019), and it was suggested by these authors that AM fungi might attenuate Cd stress by enhancing the production of thiolic compounds in AM roots.…”
Section: Responses Of V Myrtillus Roots To Cd Exposuresupporting
confidence: 75%
“…At this Cd concentration, mycorrhizal roots of V. myrtillus displayed a significantly lower Cd content with respect to non-mycorrhizal roots, supporting the hypothesis that the ERM fungus may protect the host plant by reducing metal accumulation in the plant tissues. The influence of the mycorrhizal symbiosis on heavy metal accumulation in different plant species and organs has been extensively investigated, and contrasting data have been reported for both AM and ECM symbioses, with organs of mycorrhizal plant being found to accumulate either higher or lower amounts of heavy metals than non-mycorrhizal plants (Ouziad et al, 2005;Luo et al, 2014;Coninx et al, 2017;Shi et al, 2019).…”
Section: Responses Of V Myrtillus Roots To Cd Exposurementioning
confidence: 99%
“…Two genes encoding HMA-domain proteins contained in the heavy metal transporter list were up-regulated by AM colonisation: one in Zn 0 and 5 (Medtr0041s0140) and one in all Zn treatments (Medtr6g051680) ( Figure S1b). HMA-domain proteins play key roles in transporting monovalent and divalent ions in plants, and in detoxification (27). In the zincbinding candidate list there was a Zn-binding dehydrogenase oxidoreductase gene up-regulated in all Zn treatments (Medtr8g035880) ( Figure S1c); Zn-binding alcohol dehydrogenases catalyse the reduction of acetaldehyde to ethanol, mainly in meristematic tissues such as root apices under anaerobic conditions (2).…”
Section: Identification Of Mtzip14 As a Candidate Zn Transporter Specmentioning
confidence: 99%
“…In this respect, plants have remarkable abilities to scavenge heavy metals and tolerate them at relatively high concentrations, with some species acting as hyperaccumulator employed in phytoremediation strategies for the recovery of polluted soils [74]. Mycorrhizal plants exposed to high environmental heavy metal concentrations exhibited a wide spectrum of behaviors ranging from hyper accumulation to a reduction of the uptake, also including neutral responses (see Shi et al [9] for a review). Early reports showed that zinc uptake in maize was positively affected by AM fungi, with an increase of plant growth parameters [75].…”
Section: Beyond the Mineral Nutrition: The Dual Role Of The Am Symbiomentioning
confidence: 99%
“…Major recent breakthroughs in the AM biotrophy, as the discovery of the fungal dependency on host fatty acids, represented a real paradigm shift, and stimulated the researchers to construct an updated scenario of the plant-fungal exchanges to integrate the new findings. Although both carbon and mineral nutrition in the AM symbiosis have been exhaustively reviewed by many Authors (as, for example, Casieri et al [7], Garcia et al [8], Shi et al [9], Wang et al [10]), the aim of this review is to provide the reader with a "handy guide" through the current view of the symbiotic transportome.…”
Section: Introductionmentioning
confidence: 99%